Reliance Communications : on the brink of bankruptcy - Varma, J. R. (SAGE Business cases., 2024)
The case is about a decision problem facing Shruti on identifying the relative mispricing in bonds issued by RCom in Indian Rupees (INR) and US Dollars (USD) and its stock price. As RCom’s debt troubles had increased over time, with lawsuits filed by some of its largest lenders, its stock price and credit rating had been falling consistently. On the other hand, the yields on its INR bonds had hardly moved in the meantime. After giving a brief background on RCom’s difficulties in establishing itself as one of the largest telecommunications operators in India, the case describes the behaviour of yields on RCom’s INR and USD bonds over time. It provides additional relevant financial information about RCom, including its stock price, credit rating and balance sheet variables.